ORGANIZING STUDENTS’ INDEPENDENT LEARNING IN FOREIGN LANGUAGE TEACHING THROUGH WEB QUEST TECHNOLOGY (Sciental Journal of Education Humanities and Social Sciences, 2026)
This article explores the specific characteristics of students’ independent learning activities. It highlights the application of web quest technology as an effective tool for organizing independent study within the educational system. The author argues that web quests serve as a productive form of independent work that fosters students’ creative cognition, autonomy, and the development of essential skills such as analysis, synthesis, and critical evaluation.